2014
DOI: 10.3389/fmed.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Disrupting Technology for Orthopedic Implants: What’s on the Horizon?

Abstract: The use of orthopedic implants in joints has revolutionized the treatment of patients with many debilitating chronic musculoskeletal diseases such as osteoarthritis. However, the introduction of foreign material into the human body predisposes the body to infection. The treatment of these infections has become very complicated since the orthopedic implants serve as a surface for multiple species of bacteria to grow at a time into a resistant biofilm layer. This biofilm layer serves as a protectant for the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…There is currently a requirement for novel endoprosthetic materials with optimal surface and mechanical characteristics that prevent bacterial biofilm formation avoid bacterial resistance mechanisms and mediate biocompatibility and osseointegration (10). In recent years, magnesium has emerged as a promising implant material solution.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a requirement for novel endoprosthetic materials with optimal surface and mechanical characteristics that prevent bacterial biofilm formation avoid bacterial resistance mechanisms and mediate biocompatibility and osseointegration (10). In recent years, magnesium has emerged as a promising implant material solution.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm production on implants does occur in cases whereby the medical device or surgical tools fail to sterilize effectively. Common strains such as Staphylococcus aureus , staphylococci, Pseudomonas aeruginosa (P. Ae) are the frequent suspects to produce biofilm reservoirs on prosthetic joint implants . In October 2016, Centre of Disease Control and Preventing revealed that contaminated Stöckert 3T heater‐cooler devices used during open heart surgeries in USA caused severe infections in several patients.…”
Section: Introductionmentioning
confidence: 99%
“…The surge in drug resistance in bacteria is fast surpassing the advancements in drug and antimicrobial aureus, staphylococci, Pseudomonas aeruginosa (P. Ae) are the frequent suspects to produce biofilm reservoirs on prosthetic joint implants. [4] In October 2016, Centre of Disease Control and Preventing revealed that contaminated Stöckert 3T heater-cooler devices used during open heart surgeries in USA caused severe infections in several patients. With the declining number of effective antibiotics and the potential risks of infections with medical devices, the industry is looking at alternatives to tackle bacterial growth on medical devices during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the presence of the biomaterial itself, which provides a surface that serves as anchorage for microbes and subsequent biofilm formation, constitutes the problem with regards to establishment of infection 50 . Bacteria involved in biofilm formation show increased protection from the HID system as well as an enhanced therapeutic resistance 10 .…”
Section: Pathogenesis Of Infections Associated With Implantsmentioning
confidence: 99%